A life course perspective on disability: education-to-work transitions of people with visual impairments in China - Chen, Minjie (Frontiers in Sociology, 2025)
This study adopts a life course perspective to investigate the educational and career trajectories of 26 individuals with visual impairments in China, with a focus on transitions into education and work. Through qualitative semi-structured interviews with participants recruited via snowball sampling from urban and rural areas, thematic analysis identified five patterns of education-to-work transitions, guided by life course principles. Findings reveal delayed educational transitions, high dropout rates (53.88% during compulsory education), and predominant entry into the tuina (Chinese medicine massage) industry due to societal stereotypes and structural constraints. Urban participants accessed non-massage skills through family support, enabling diverse careers, while rural participants faced financial pressures to pursue tuina for stability, illustrating the principle of linked lives. The study contributes to Chinese disability studies by applying life course theory in a non-Western context, highlighting interactions between timing, sequence, agency, and social forces. Policy implications include expanding inclusive preschool access, mainstream school accommodations, and diverse tertiary programs to broaden career options and challenge vocational stereotypes. Future research should prioritize women with visual impairments to address gender disparities in educational access.